Harmonized Latin American Innovation Surveys Database (LAIS): Firm-level microdata for the study of innovation - Fernando Vargas; Charlotte Guillard; Monica Salazar; Gustavo A. Crespi (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2022)
This paper provides the methods through which the first version of the Harmonized Latin American Innovation Surveys database (LAIS) was built. LAIS, which is made freely available through the Inter-American Development Bank, contains nearly 690 variables and 119,900 observations at the firm level from 30 national innovation surveys conducted between 2007 and 2017 in 10 Latin American countries, increasing the number of countries of the region with publicly available microdata. This paper describes how, starting from significantly different survey methods and questionnaires between countries, criteria were applied to identify and select variables from different surveys measuring the same underlying concept. It also discusses and guides how differences in survey methodologies may affect comparisons even after the harmonization of variables. LAIS includes data on innovation activities expenditures, sources of information and collaborations for innovation, innovation obstacles, outputs and effects, protection of innovation results, and general firm characteristics. Since LAIS significantly decreases the cost of making data comparisons between countries, it will allow more scholars to research innovation in Latin American firms and to tackle long-standing unanswered questions about the importance of framework conditions in LAC for innovation decisions in firms. The dataset and supporting documentation are available at: http://dx.doi.org/10.18235/0004040
Keywords: O10; O12; O31; O32; C81; 330; cross-country data; innovation; innovation processes; innovation surveys; microeconomics; Latin America